(untitled) (INNOVATIVE ECONOMY, 2023)
Honcharenko I.V. IMPLEMENTATION OF CIRCULAR ECONOMY APPROACHES IN THE TERRITORIAL COMMUNITIES OF THE REGION Purpose. This article aims to investigate the implementation of circular economy practices based on existing empirical studies. Methodology of research. General scientific and special methods were used in the research process, in particular: induction and deduction – at the stage of collecting, systematizing and processing the necessary information; analysis and comparison - in the process of identifying the reflection of waste management problems in the strategic documents of the selected communities and the characteristics of the implementation of the principles of the closed cycle economy; abstract and logical – to form theoretical conclusions. The choice of communities fell on the sampled sample because they represent city, village, and settlement species and evenly geographically located territory of the Mykolaiv region. Findings. It has been found that in the existing strategic documents of the analysed communities solving the problem of waste management has been identified among the priority tasks. None of the analysed strategies specifies successful practices that implement the principles of a closed cycle economy. Two city communities have legal landfills for the accumulation of solid waste but do not use technologies of sorting, processing, and energy production, instead, there is a threat of exhaustion of the repository resource. Four rural communities only declared the need to allocate a specially equipped waste landfill for each settlement and began educational work among the citizens regarding the sorting of garbage, the danger of its burning, and awareness of its value as a resource for reuse or processing. Among the particularly alarming conditions, the low level of activity of community residents in solving existing problems is found, so the involvement of citizens is to be increased first of all. Originality. The substantiation of the expediency of introducing closed-loop economy approaches for territorial communities has been further developed. Practical value. Proposals, which were formulated on the base on the results of the study, can be used by representatives of local governments to involve community residents in the implementation of closed-loop economy practices for the socio-economic development of communities. Key words: closed-loop economy, resources, waste, linear model of economy.